ANALISIS FUNGSI KEPEMIMPINAN (STUDI KASUS PADA KANTOR SEKRETARIAT DPRD KOTA LUBUKLINGGAU) - Subuh Hidayat (LPPM UNIVERSITAS BINA INSAN, 2017)
This study aims to determine the application of leadership functions in the Lubuklinggau City DPRD secretariat office. In this study using primary and secondary data sources, namely data collected by authors from books and literature that are relevant to leadership functions. The results of the study show that instructive function, the leader sometimes directs how to do the command, the time to start and carry out the work, and report the results, as well as where to do the command, applied properly. Likewise the consultative function is that the leader uses consultative functions quite well, even though there are some who have not received the turn to be invited to communicate because the employees are less open. Participatory functions have been implemented well even though there are still a small number who have not been involved. delegate function, every delegation of authority or setting a decision by the leader in accordance with the expertise possessed by the employee has been implemented well, although there is a small portion there is still no authority delegation given the ability and responsibility of employees who have not been good. The control function, that is, the leader has provided guidance, direction, coordination, and supervision of all employee activities at the Lubuklinggau City DPRD Secretariat office, although there are still a small number that are not good, this is because employees are still undisciplined, lazy , and often do not work. The control function is said to be good.